Seed quality of lablab bean [Lablab Purpureus (L.) Sweet] influenced by seed maturity and drying methods - Hanapiah, Nurul Fatin Hanani (2020)
Lablab bean or ‘Kacang sepat’ is a food crop originating from India and commonly found in tropical area such as Indonesia, Thailand and Philippine due to its adaptability. However, in Malaysia lablab is grown as a backyard crop and area cultivation with this crop is still limited. Due to the high protein content (18-25%) and multipurpose nature of the crop whereby as all parts can be consumed except the roots, lablab can be one potential commercial vegetables. Therefore, to increase lablab cultivation, good quality seeds should be a prerequisite. Harvesting at the ideal development stages produces high quality seeds. The first part of the study was conducted to access pod and seed physical characteristics of two types of lablab bean, dark purple (MDI 12839) and green with purple edge (MDI 12842). Plants were grown using standard cultural practices. Pods and seeds were collected at ten different maturity stages (5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 Day after anthesis (DAA). Seed moisture content and seed dry weight was carried out to know the quality of seeds. The results showed significance between different maturity stages in all parameter studied. Pods and seeds showed significant different in size, colour and protein content. Seeds harvested at 20 DAA (Day after anthesis) showed maximum seed size and pod. The seeds from both types of lablab had attained physiological maturity (PM) at 30 DAA with moisture content was 27.3% for lablab dark purple and 23.3% for lablab green with purple edge. Lablab dark purple was not used in the second study. In this study, both types of drying, sun and oven drying managed to reduce seed moisture content. Harvested seeds at PM (30 DAA) and subjected to sun and oven method obtained maximum germination percentage, 89% and 91% respectively, while fresh seeds only 78%. Result indicated that the germination percentage of lablab improved, regardless of the using any drying methods. In addition, seed vigour and seedling growth also showed significant different on interaction between maturity stages and drying method.